The profitability of bank–borrower relationships - Ergungor, O. Emre (Journal of Financial Intermediation, 2005)
This paper investigates the profitability of relationship banking within the context of small business loans made by community banks. Theory implies that competition reduces the benefits of bank-borrower relationships, making relationship loans more risky and less profitable. I present evidence for community banks that is consonant with this implication.